Commoning and site-specific environmental performance in Marseille - Rebecca Free; Mark Ingram (Sinais de Cena)
Given that our current environmental crisis is, as Amitav Ghosh argues, “in every way a collective predicament”, a critical question for discussions of the ecological impact of the arts is their role in fostering the kinds of collaborative forms of action called for to address environmental challenges. Such discussions include Baz Kershaw’s criticism of the anti-ecological “production of spectators” by theatres, and Brian Kulick’s more recent argument that theatre generates moments of collective attentiveness that might contribute to collaboration beyond the performance event.